Virtual reality in managing dental pain and anxiety: a comprehensive review - Fan, Lin; Zeng, Jie; Ran, Longkuan; Zhang, Chao; Wang, Jing; Yu, Cong; Zhao, Nan (Frontiers in Medicine, 2023)
Objectives: Aimed to identify, analyze, and summarize the clinical efficacy of virtual reality (VR) distraction therapy for oral treatment in different hospital settings in contrast to medical interventions that induce anxiety and pain. Furthermore, this review aimed to determine the implications for research and clinical practice of VR distraction therapy. Data: This review investigated the clinical efficacy of VR in the oral treatment of procedural pain or anxiety. Quality assessment of the included studies was conducted. A narrative synthesis of the collected data was performed. Sources： Literature from six electronic databases was searched for a comprehensive review, namely, the Cochrane Oral Health's Trials Register, Cochrane Central Register of Controlled Trials (Central), MEDLINE (PubMed), EMBASE, Scopus, and Web of Science.Study selection: 1,522 patients aged between 0 and 60 years who used VR during dental treatment were included in this review. Among these studies, 8 and 14 studies comprised adult and pediatric patients.Overall, the reviewed studies underscore the efficacy of VR to mitigate pain and anxiety in the context of dental treatment. VR is an innovative pain and anxiety management approach that facilitates dental treatment patients to immerse themselves in a virtual world while using distractions to reduce pain and anxiety.Clinical significance: VR is an effective and novel non-pharmacological method of behavioral management that contributes to improving medication safety for dental patients. VR as a distractive approach can reduce the fear associated with medical interventions and prevent severe pain sensitivity, anxiety, and medical avoidance among adults and children.